Rancang Bangun Sistem Informasi Geografis Lokasi Debitur Berbasis Web - Natalia Magdalena R Mamulak (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2018)
There are many problems in the process of credit payment, for example, to find out the location of the debtor who is late in the payment, debtors live nomads since they have only temporary ID Cards.his one of the reasons for the debt collectors having difficulties to find them in order to ask their payment. Therefore, it is important to build a geographic information system that can assist the employee for searching the debtor location. The tools for building this application are using PHP 7 programming language and MySQL database. This study is also using an expanding method of Software Development Life Cycle (SDLC) waterfall model. There are five stages of waterfall model i.e. analysis, design, coding, testing, and maintenance. The result provides an application for detecting the location of the debtors who are late on payment.